Systemic Conflicts of the Constitutionalism and Possible Solutions - Ayvazyan , V. (Bulletin of Yerevan University C: Jurisprudence, 2018)
As part of a comprehensive study of the Genesis of Systemic Conflicts in Constitutional-Legal Regulation, the author has published a number of articles aimed at systematizing methodological tools within the emerging new scientific discipline "Legal Conflictology". This article is a logical addition to the thematic analytical blocks separately disclosed in the mentioned articles.
Keywords: constitutionalism, rule of law, constitutional-legal regulation, systemic conflicts, legal conflictology, essence of law, format of constitutionalism